Stabilization Policies in a Growing Economy - Stein, Jerome L.; Nagatani, Keizo (Review of Economic Studies, 1969)
Jerome L. Stein, Keizo Nagatani; Stabilization Policies in a Growing Economy1, The Review of Economic Studies, Volume 36, Issue 2, 1 April 1969, Pages 165–